Kajian Pengeluaran Biaya Kesehatan pada Pasien Stroke: A Narrative Review - Rohmah, Syifaur (Journal Pharma Saintika, 2025)
Abstract: Stroke treatment is very expensive. The number of stroke cases increases every year. Policymakers need data regarding the amount of costs incurred for stroke treatment to develop problem-solving strategies related to the financial impact of stroke. This study aims to determine the health costs of stroke patients in Indonesia. Stroke treatment costs were taken from the Garuda Portal database and National Library e-resources using the keywords "cost" AND "stroke"; “cost of illness” AND “stroke”. The results of the narrative review showed that 15 articles were included in the inclusion criteria. Cost expenditure analysis is divided into three categories, direct medical costs, direct non-medical costs, and indirect costs. The cost of stroke treatment varies greatly between hospitals. Drug and hospitalization costs are the largest components of stroke expenditure. The factors that influence stroke treatment costs include age, length of stay, secondary diagnosis, severity, comorbidities and class of treatment.